(untitled) (Journal of the College of Basic Education, 2025)
After the end of World War I, the regions of the Arabian Peninsula were exposed, like the rest of the other Arab countries that were under Ottoman rule for a long period of time, reaching about four centuries, to many political, economic and social problems. After the end of the war, they emerged exhausted to move to the stage of independence and highlight their independent Arab and national character. The establishment of the Kingdom of Saudi Arabia at that time, which went through many great steps and actions, ended with the unification of the Kingdoms of Najd and Hejaz into one state, with the efforts of King Abdulaziz Al Saud, the founder, who laid the basic building blocks for building a modern, advanced state. To rise from the backward reality imposed on him by the long Ottoman occupation, King Abdulaziz Al Saud began working with all diligence, diligence and sincerity to transfer Saudi society from a life of misery, movement and wandering to a life of stability, which King Abdulaziz Al Saud saw as the first step to launch society towards comprehensive economic development. His first project to settle the Bedouins was a good example of this. After the success of the settlement project, the economic and social development of the emerging Saudi society took off at that stage, until the discovery of oil was a reason for accelerating the wheel of economic and developmental progress in the Kingdom of Saudi Arabia. And for Saudi society to move economically leap Great quality.